(untitled) (Physical Education, Health and Social Sciences, 2026)
Barley (Hordeum vulgare L.), a key cereal crop with moderate tolerance to abiotic stresses, faces escalating threats from soil salinity (affecting 10% of irrigated lands) and drought, which collectively impair >50% of global crop yields. This comprehensive review synthesizes the multifaceted role of biochar a carbon-rich pyrolytic amendment in enhancing soil properties and barley resilience under these conditions. Biochar’s efficacy depends on feedstock (e.g., crop residues, woody biomass, manures) and pyrolysis temperature (300–650°C), influencing its porosity, surface area, pH, and functional groups. It ameliorates soil physicochemical traits by reducing bulk density, boosting aggregate stability, elevating water holding capacity (up to 33% increase in plant-available water), and lowering electrical conductivity through Na+ and Cl- adsorption. Nutrient dynamics are optimized via enhanced cation exchange capacity, improved K+/Na+ ratios, and higher utilization efficiencies (e.g., 20–53% for N, 38–230% for P). Physiologically, biochar preserves relative water content, chlorophyll integrity (up to 72% increase), stomatal conductance, and photosynthetic efficiency, leading to morphological gains (e.g., 13–57% taller plants) and yield enhancements (up to 53% higher grain weight). Antioxidant defenses are bolstered by reduced reactive oxygen species and elevated enzyme activities (SOD, POD, CAT), while microbial synergies (e.g., with PGPR) further promote rhizosphere health and greenhouse gas mitigation. Socio-economic barriers to adoption include high production costs and scalability issues, yet integrated strategies combining biochar with gypsum, compost, or nano-forms offer sustainable pathways for arid agriculture. Overall, biochar emerges as a versatile tool for climate-resilient barley production, though context-specific optimization is essential.